Aging and Bioethical Aspects of Mechanical Ventilation in Terminal Disease (Revista Iberoamericana de Bioética, 2020)
Scientific and technological development is leading to the emergence of certain techniques that increase life in chronic disease cases that usually lead to a terminal disease during aging. These techniques are increasingly included under the heading of life support, and among the most frequent is mechanical ventilation, which is the source of numerous bioethical dilemmas. Despite this, it is necessary to have a series of considerations as useful tools for health professionals.
Keywords: terminal illness; aging; mechanic ventilation; end of life